Racial disparities in the diagnosis of disruptive behavior disorders: a U.S. national inpatient sample analysis - Savage, William M.; Saint-Hilaire, Sidney A.; Shah, Mansi; Lugo-Candelas, Claudia (Frontiers in Psychiatry, 2024)
Disruptive behavior disorders (DBDs) are comprised of conduct disorder and oppositional defiant disorder. Limited literature exists on the demographics of patients diagnosed with these conditions. Despite the clinical overlap of DBDs and attention-deficit hyperactivity disorder (ADHD), there is a stark divergence in the treatment and societal accommodation for these two diagnoses, amplifying the importance of this diagnostic challenge. Thus, potential diagnostic differences must be urgently and rigorously explored. Small, regional studies have reported potential "racial" disparities in the diagnosis of DBDs, especially when compared to the diagnosis of ADHD. Our study uses the National Inpatient Sample (NIS) database to provide the largest, most comprehensive investigation of "racial" disparities in the diagnosis of DBDs. Discharge data from 700,770 pediatric inpatients (mean age = 9.32 years) were included in this analysis. To explore potential disparities among children with symptoms in this area of clinical overlap, we assessed the relationship of "race" and the diagnosis of DBDs. Among the subgroup of pediatric inpatients diagnosed with ADHD or a DBD, Native American (OR = 2.18; 95% = 1.76, 2.70), Asian (OR = 1.88, 95% = 1.56, 2.26), Black (OR = 1.40; 95% = 1.32, 1.48), and Hispanic (OR = 1.20; 95% = 1.12, 1.28) "race" correlated with DBD diagnosis (Figure 1). By highlighting these diagnostic disparities, this study raises essential questions about race and the diagnosis of DBDs.